Comparison between Clegg Impact Soil Tester and hoof impact shock measurements on 13 surfaces used for training trotters or sport horses - Munoz-Nates, F.; Pourcelot, P.; Van Hamme, A.; Martinot, J.; Pauchard, M.; Nouvel, M.; Ravary-Plumioen, B.; Chateau, H.; Crevier-Denoix, N. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Sport surfaces can be a risk factor for injury in human and equine athletes. It was recently demonstrated that more severe lesions occurred in young trotters after 4 months of training on a hard track, compared to a soft one (Crevier-Denoix et al., 2016). Biomechanical measurements performed on both tracks revealed that maximal forces and loading rates, as well as vertical deceleration peak at impact (impact shock), were significantly larger on the horses exercising on the hard track. Although the respective influence of these biomechanical variables on injury occurrence is not established yet, it is likely that repetitive high impact shocks contribute to risk for subchondral bone damage and even fracture in the distal limb segments, as well as for superficial digital flexor tendon injury, although maximal loading and loading rates are probably major risk factors for severe limb injuries.